Assessing Interactions between Multiple Geological CO2 Storage Sites to Optimize Capacity in Regionally Extensive Storage Sandstones. (July 2017) - Akhurst, Maxine; Mallows, Tom; Pearce, Jonathan; Mackay, Eric
Abstract: The potential resource for carbon dioxide (CO2 ) storage in strata underlying the North Sea is mostly within brine-saturated sandstone formations which are each many hundreds to thousands of square kilometres in extent. The immense potential to store CO2 in these rocks can only be fully achieved by the operation of more than one injection site within each formation. A UK North Sea case study anticipates the operation of two injection sites in the Captain Sandstone and assesses any interaction between the injection sites. Technical investigations to optimize the storage capacity in a regionally extensive North Sea sandstone by the operation of more than one injection site within a storage formation [1] are summarised: geological modelling; geomechanical modelling; simulation of CO2 injection; monitoring planning. The UK case study includes the Goldeneye Field, the storage site investigated for the planned Peterhead CCS project. An injection scenario was examined that comprised an initial project storing within a depleted hydrocarbon field structure followed by a second injection site within the surrounding saline aquifer. The research investigations were targeted to identify and reduce any perceived concerns specific to the operation of two sites by a risk assessment-led process. Requirements for a monitoring plan specific to a multi-user storage formation, based on the prediction of storage site performance, were also developed. Generic learning applicable to any suitable multi-user storage sandstone was captured, from the process followed and the technical knowledge acquired, on the characterisation of extensive sandstone formations, management of the planned injection operations and monitoring planning.